2014
DOI: 10.1007/s12194-014-0273-2
|View full text |Cite
|
Sign up to set email alerts
|

Spatial resolution measurement for iterative reconstruction by use of image-averaging techniques in computed tomography

Abstract: The purpose of our study was to investigate the validity of a spatial resolution measuring method that uses a combination of a bar-pattern phantom and an imageaveraging technique, and to evaluate the spatial resolution property of iterative reconstruction (IR) images with middle-contrast (50 HU) objects. We used computed tomography (CT) images of the bar-pattern phantom reconstructed by the IR technology Adaptive Iterative Dose Reduction 3D (AIDR 3D), which was installed in the multidetector CT system Aquilion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 26 publications
0
23
0
Order By: Relevance
“…This yielded a sufficiently high contrast-to-noise ratio (CNR) of the averaged image (≥25), according to a report in which the image averaging technique was used to improve the evaluation accuracy of the IR resolution property of a bar pattern phantom [9]. Our preliminary experiments involving this high CNR condition indicated that the standard deviation for five measurements fell within 0.007 for frequency ranges <10% MTFTask.…”
Section: Phantom Image Data Analysismentioning
confidence: 73%
“…This yielded a sufficiently high contrast-to-noise ratio (CNR) of the averaged image (≥25), according to a report in which the image averaging technique was used to improve the evaluation accuracy of the IR resolution property of a bar pattern phantom [9]. Our preliminary experiments involving this high CNR condition indicated that the standard deviation for five measurements fell within 0.007 for frequency ranges <10% MTFTask.…”
Section: Phantom Image Data Analysismentioning
confidence: 73%
“…For quantitative evaluations, non‐helical scanning with an 80 × 0.5 mm 2 detector configuration was performed to eliminate the influence of table movement on the image‐averaging process, as described later 17. For qualitative evaluation, helical scanning (pitch factor, 0.844) with a 32 × 1.0 mm 2 detector configuration was used, assuming clinical settings.…”
Section: Methodsmentioning
confidence: 99%
“…The acrylic phantom was placed at the isocenter of the CT scanner. To acquire low‐noise images for the MTF task analysis, 100 or more scans were performed with the same table position for each radiation dose level and these were averaged for each protocol using image‐averaging techniques 17. Furthermore, images were reacquired after the liquid in the phantom was adjusted with diluted contrast medium (60 HU) to obtain a contrast of 10 HU between background and soft tissue (70 HU).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This technique has been widely used for MTF measurements of IR images. Most of the studies using this technique computed the average of the consecutive cross‐sectional images of the cylinder and/or the average of many images acquired from repeated scans to improve the signal‐to‐noise ratio …”
Section: Introductionmentioning
confidence: 99%